Enhancing Regional Development with Startup Ecosystems - Lytvynskyi, R. (Економічний вісник Донбасу, 2023)
Regional development based on innovation plays a significant role in stimulating economic growth in the wartime and postwar periods. The creation of innovative ecosystems that support the development of startups and small innovative enterprises ensures the formation of a favorable business climate in the regions and attracts investment, reduces the dependence of regions on traditional industries, creates highly skilled jobs and develops entrepreneurial talent. The purpose of the study is to determine the features of startup ecosystems, their impact on regional development, and to identify the factors of successful functioning of such ecosystems based on the analysis of foreign experience. The article analyzes the experience of formation and development of startup ecosystems in Sweden and Finland, identifies their unique advantages, historical achievements, and current trends. Sweden has a high level of global competitiveness due to active support from the public sector and a favorable business climate. Finland is known for its innovative potential, stable business environment, and attractive conditions for startups and investors. The results of the study demonstrate the sustainable success and prospects for further growth of both ecosystems on an international scale. The study found that despite Sweden and Finland's tremendous achievements in the field of startup development, most of these structures are in the capitals of the countries. It is concluded that although this practice is effective on a national scale, it does not have a qualitative impact on regional development. In the post-war period, Ukraine has a unique opportunity to intensify regional development by mobilizing the potential of specialists who have relocated from the occupied and frontline territories to other regions of the country. The process of forming startup ecosystems around these professionals can give impetus to the development of new types of business or innovative transformation of traditional sectors of regional economies. To successfully implement this approach, a set of appropriate regulatory, organizational, and infrastructural measures must be implemented.